2016
DOI: 10.21037/gs.2016.01.06
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic and robotic parathyroidectomy in patients with primary hyperparathyroidism

Abstract: Primary hyperparathyroidism (PHPT) is one of the most common endocrine disorders for which parathyroidectomy is the most effective therapy. Until late 1970s, the standard approach to parathyroidectomy was a four-gland exploration using a large skin incision. However, 80 to 85 percent of cases of PHPT are caused by a single adenoma. As such, the concept of performing a bilateral exploration in order to visualize all four glands has been argued to be excessive since in the majority of cases, there is only one ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
24
0
10

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 37 publications
0
24
0
10
Order By: Relevance
“…This approach was required to identify which of the parathyroid glands was clinically abnormal and to ensure that additional abnormal glands were not overlooked. BNE with four‐gland dissection, however, required a large cosmetically less favorable incision, exposed both recurrent laryngeal nerves (RLNs) to potential iatrogenic injury, and subjected the patient to the risk of permanent hypoparathyroidism …”
Section: Introductionmentioning
confidence: 99%
“…This approach was required to identify which of the parathyroid glands was clinically abnormal and to ensure that additional abnormal glands were not overlooked. BNE with four‐gland dissection, however, required a large cosmetically less favorable incision, exposed both recurrent laryngeal nerves (RLNs) to potential iatrogenic injury, and subjected the patient to the risk of permanent hypoparathyroidism …”
Section: Introductionmentioning
confidence: 99%
“…Endoscopic surgery has been adopted in most institutions for parathyroid gland removal, and several studies have demonstrated reduced postoperative pain and improved cosmetic outcome as compared to traditional open approach (1). Application of robotic technology for parathyroid removal has been less extensively studied and its use has not been widely adopted.…”
Section: Introductionmentioning
confidence: 99%
“…Application of robotic technology for parathyroid removal has been less extensively studied and its use has not been widely adopted. Previous studies have documented the safety of the procedure with the advantages of greater image magnification, gasless technique, and a hidden axillary incision (1)(2)(3)(4). Herein we present our technique of robotic transaxillary parathyroidectomy at an academic institution.…”
Section: Introductionmentioning
confidence: 99%
“…In the 1970s, parathyroid resection was done through a large incision made in the neck that allowed for full exploration and exposure of all four parathyroid glands. This method had a success rate of 97% there were complications in 1-2% of cases [1]. Typically, parathyroid adenomas are found only in a single gland, and targeted therapy can be performed that removes only the pathological gland.…”
Section: Introductionmentioning
confidence: 99%
“…Typically, parathyroid adenomas are found only in a single gland, and targeted therapy can be performed that removes only the pathological gland. The 1980s saw the introduction of first one-sided two-gland, and then single-gland surgeries, made possible by the development of more advanced preoperative imaging methods and the introduction of intraoperative parathyroid hormone monitoring [1,2].…”
Section: Introductionmentioning
confidence: 99%